SUVO’TLARNING EKOLOGIYASI VA AHAMIYATI - Qo’ldosheva Karimaxon Baxtiyorjon qizi, Tojiboyev Murodali Umaraliyevich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this work, the ecology of algae and their importance in the ecosystem of water bodies are studied. Algae play an important role in improving water quality by stabilizing biochemical processes in the aquatic environment, producing oxygen, accumulating organic matter, and filtering harmful substances. They create habitat and food source for aquatic organisms and provide biological diversity. Algae as a bioindicator are also important in assessing the ecological status of water bodies. The importance of this topic is closely related to the preservation of water ecosystems and the preservation of natural balance.